Preliminary Study: Development of STEM-Based E-Students Worksheet to Improve Learners' Science Literacy Skills - Nurul Hasanah Daniyah Putri; Ramli Ramli (Postgraduate, University of Mataram, 2023)
The purpose of this study was to describe the results of the needs analysis for the development of e-Students Worksheet based on the STEM approach to improve the science literacy skills of students in several high schools in Padang City. This research design uses the R&D method by using the Plomp development model which consists of three steps, namely: 1) preliminary research; 2) prototyping phase, and 3) assessment phase. The instrument used in this research is a questionnaire validation sheet filled out by educators and students. Based on the analysis of the results of preliminary data observations conducted in several high schools in Padang City, the results obtained are in the analysis of graduate competency standards, assessment, learning activities have an average percentage with a very good category. However, in the analysis of students, the STEM approach, the use of electronic teaching materials, and science literacy generally have an average percentage that is in the sufficient category. To overcome the existing problems educators can develop STEM-based e-Students Worksheet to improve students' scientific literacy